The Entrepreneurial instinct : how everyone has the innate ability to start a successful small business - Mehta, Monica (New York : McGraw Hill Education, 2013)
"This book gets rid of the last excuse of the would-be entrepreneur: fear. By showing how you can work with your brain chemistry rather than against it. The Entrepreneurial Instinct helps you take smarter risks with less angst. It obliterates a lot of the conventional wisdom around entrepreneurship and shows what it really takes to succeed." - Kimberly Weisul
Introduction -- How Sunil and Rita made millions -- Decoding the framework of the instinct-driven entrepreneur -- The entrepreneur's innate risk-taking edge -- The chemical that drives risk taking -- The personality traits of the self-made -- The source of fear -- Turning off your red light -- Take rewarding risks -- Launching a business by using instinct -- Finding inspiration -- Create a cycle of productivity -- Shoot first, aim later -- Don't spend a dime -- Before you quit your job -- How beliefs define reality.
Includes bibliographical references and index.
Keywords: NEW BUSINESS ENTEPRISES